Творчість полтавського бандуриста Івана Коваля - Головня, Л. (Народна творчість та етнографія, 2006)
Серед діячів бандурного мистецтва Полтавщини, несправедливо обійдених увагою у сучасному українському мистецтвознавстві, вирізняється постать Івана Андрійовича Коваля (1936—2000 рр.) — віртуозного бандуриста, диригента, хормейстера, автора вокально-інструментальних творів і аранжувань українських народних пісень, талановитого педагога, активного громадського діяча. In this article the author shows first in Ukrainian art science the outstanding life and works of Ivan Koval (1936-2000), who was a highly skilled musician, a talented pedagogue, an experienced choir master, an active public man, an author of numerous vocal works and arrangements of Ukrainian folk songs. Appeal to his many-sided creation nowadays is caused not only by the enthusiasm, gratitude and respect of his colleagues and pupils, but also by the significant event - the 70th anniversary of the musician, which was celebrated in Poltawa in October 2006.